Performance Analysis of an ESP32-Based Integrated Smart Home Access System: A Laboratory Scale Study - Fikri, Ryan; Dwinggo Samala, Agariadne; Faiza, Delsina; Almasri, Almasri (Universitas Negeri Padang, 2025)
This study developed and evaluated an integrated Internet of Things (IoT)-based access control system that unifies residential gate operation, garage door automation, and garage lighting within a single platform. Conventional home automation deployments typically address only one function at a time, resulting in fragmented control and limited interaction between subsystems. Compared to prior smart home implementations that focus on single subsystems, the proposed platform jointly manages gate, garage door, and lighting and reports scenario-based reliability metrics. To address this gap, the proposed system used an ESP32 microcontroller as the central controller, ultrasonic distance sensors for vehicle detection, servo motors for mechanical actuation, and a relay module for lighting control. A mobile application built with the Blynk platform provided real-time monitoring and remote control via smartphone. The prototype was tested under three scenarios-manual mobile control, fully automatic sensor-triggered operation, and combined operation-with 20 repeated cycles per scenario. Performance metrics included servo actuation time, communication latency between the mobile application and the ESP32, sensor accuracy, and operational reliability. The gate and garage door achieved opening times of approximately 1.0-1.2 s and 1.5 s, respectively, while end-to-end communication latency remained between 300 ms and 480 ms across all tests. Ultrasonic distance measurements showed a maximum error of 1.8 cm and an average error below 1.2 cm, with no system failures in any scenario. These results demonstrate that the integrated design is technically feasible, reliable, and suitable as a cost-effective foundation for residential access control. Future work will focus on scaling the prototype toward full-size installations and extending integration with additional smart home services.